Simultaneous Measurements of the Vehicle, Track, and Soil Vibrations at a Surface, Bridge, and Tunnel Railway Line - Lutz Auersch (Shock and Vibration)
A complex measuring campaign has been performed including the simultaneous measurement of vehicle, track, and soil vibrations during train runs at 16, 25, 40, 63, 80, 100, 125, 140, and 160 km/h and impulse measurements of the passenger car, three track sections, and the soil. A ballast track on the soil surface and on a concrete bridge has been investigated as well as a slab track in a tunnel. The evaluation and comparison of all these data show a generally good agreement for all components if the strong low- and high-frequency cut-off characteristics of the layered and damped soil are incorporated. There is a strong causal correlation between the vehicle and the soil by the dynamic excitation forces and a weak relation between the track and the soil by the axle-sequence spectrum of the train. However, the similarity between the axle-impulse spectrum observed at the track and the spectra of the ground vibration leads to the special excitation component of “scattered axle impulses” which is predominant at the far field points of the soil.